Ophthalmic release of in situ gel Ciprofloxacin HCl based on combination of Hypromellose and HPC - Yoga Windhu Wardhana; Wieke Budiati; Rizky Dwi Oktavia; Kalista Tritama Widyanti; Insan Sunan Kurniawansyah; Yedi Herdiana (Indonesian Journal of Pharmaceutics, 2021)
The development for ophthalmic delivery was purposed to achieve optimum drug loading for ocular therapeutic benefits. An adequate dose of the drug is needed to absorb in the conjunctival sac to take effect. In situ gel preparation was expected to provide these needs with the polymer aid that makes the droplets suddenly coagulate in the eye area to maintain the drug dose. The in situ gel dosage form is desired to overcome the poor bioavailability of conventional ciprofloxacin HCl eye drops on the market. Thus, this work was studied using two cellulose polymers such as hydroxyl propyl cellulose (HPC) and hydroxypropyl methylcellulose (HMPC) as a gelling forming agent.  The effect of the in situ ophthalmic quality of the gel due to the two individual polymers separately and their combined use was investigated. The in situ gel quality includes the ability of gel-forming under the influence of varying temperature and stirring frequency difference (as a rheological study) was tested together with the drug release model model. Other ophthalmic preparation quality parameters such as clarity, pH measurement, drug content determination, sterility, and antibacterial activity have been evaluated. However, overall in situ gel formulation developed was of better quality compared to the conventional one. Consideration of the choice of cellulose derivative polymer type is seen to affect the quality of controlled release kinetics models.Keywords: Ophthalmic gel, Ciprofloxacin HCl, HPMC, HPC, Drug release kinetics